2018
DOI: 10.1002/qua.25593
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of nitrous oxide (N2O) by 1, 4, 2, 5‐diazadiborinine: A DFT study

Abstract: The role of nitrous oxide (N2O) in stratospheric ozone depletion and as a greenhouse gas has inspired the scientific community across the globe in understanding the capture, activation, and decomposition of it. Very recently people have started fixing N2O using frustrated Lewis pairs. In this study, we have tried to analyze the fixation of N2O by 1,4,2,5‐diazadiborinine by applying various computational tools and techniques associated with density functional theory. 1,4,2,5‐Diazadiborinine is taken as the fixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Nitrous oxide reacts with FLP and produces an addition product having LB–NN–O–LA linkage, e.g., t Bu 3 P­(N 2 O)­B­(C 6 F 5 ) 3 is produced by reaction of N 2 O with P t Bu 3 /B­(C 6 F 5 ) 3 pair . Our recent DFT computation on the activation of N 2 O by an ambiphilic diazodiboronine gives three products (2–4 in Figure ). All the newly generated B–O and B–N bonds are partly covalent as revealed by electron density analysis.…”
Section: Small Molecules Activationmentioning
confidence: 98%
See 2 more Smart Citations
“…Nitrous oxide reacts with FLP and produces an addition product having LB–NN–O–LA linkage, e.g., t Bu 3 P­(N 2 O)­B­(C 6 F 5 ) 3 is produced by reaction of N 2 O with P t Bu 3 /B­(C 6 F 5 ) 3 pair . Our recent DFT computation on the activation of N 2 O by an ambiphilic diazodiboronine gives three products (2–4 in Figure ). All the newly generated B–O and B–N bonds are partly covalent as revealed by electron density analysis.…”
Section: Small Molecules Activationmentioning
confidence: 98%
“…Nitrous oxide reacts with FLP and produces an addition product having LB−N�N−O−LA linkage, e.g., tBu 3 P(N 2 O)-B(C 6 F 5 ) 3 is produced by reaction of N 2 O with PtBu 3 /B(C 6 F 5 ) 3 pair. 46 Our recent DFT computation 47 3 Lewis pair shows that the strength of LA mainly governs the thermodynamics of the reaction just like the case of CO 2 activation. 48 A transition metal (TM) interacts with an ambiphilic borane/ phosphine ligand by donating one of its filled d-orbital electrons to the borane and accepting electron to an empty d-orbital.…”
Section: Small Molecules Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…to reduce the use of expensive and toxic transition-metal-based catalysts. Apart from H 2 activation, FLPs may activate and react with other small molecules like CO 2 , N 2 O, CO, NO, SO 2 , C 2 H 4 , C 2 H 2 , etc. , Thus, FLP-assisted small molecule activation helps in designing and synthesizing new molecules. Moreover, carbon monoxide (CO) and isonitrile (CNR) can coordinate with intramolecular FLPs to give five-membered heterocyclic compounds, where the carbon centers of CO and CNR can cooperatively bind with the LA and LB centers of FLPs. , In an earlier study, Stephan and co-worker reported the activation of ethylene and other alkenes by nonbridged P/B FLP, yielding alkanediyl-linked zwitterionic phosphonium borates, and they suggested that the reaction is initiated by the activation of alkenes by Lewis acidic borane and then the addition of Lewis basic phosphine takes place .…”
Section: Introductionmentioning
confidence: 99%
“…FLPs may also activate other molecules such as NO, SO 2 , CO 2 , N 2 O, CO, C 2 H 4 , C 2 H 2 etc. (Mc Cahill et al, 2007 ; Moemming et al, 2009 ; Dureen and Stephan, 2010 ; Appelt et al, 2011 ; Cardenas et al, 2011 ; Kolychev et al, 2012 ; Sajid et al, 2014 ; Stephan and Erker, 2014 ; Ghara and Chattaraj, 2018a , b ). FLP assisted small molecule activation thereby offers new synthetic opportunities.…”
Section: Introductionmentioning
confidence: 99%